2018
DOI: 10.1016/j.jmva.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic partial least squares model: Identifiability, estimation and application

Abstract: With a rapid increase in volume and complexity of data sets, there is a need for methods that can extract useful information, for example the relationship between two data sets measured for the same persons. The Partial Least Squares (PLS) method can be used for this dimension reduction task. Within life sciences, results across studies are compared and combined. Therefore, parameters need to be identifiable, which is not the case for PLS. In addition, PLS is an algorithm, while epidemiological study designs a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Extending latent variable methods to probabilistic models is not new. PCA was extended to Probabilistic PCA in [4], and PPLS [10] was proposed to provide a probabilistic framework for PLS. It has been shown that the probabilistic counterpart has a lower bias in estimation and is robust to non-normally distributed variables [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending latent variable methods to probabilistic models is not new. PCA was extended to Probabilistic PCA in [4], and PPLS [10] was proposed to provide a probabilistic framework for PLS. It has been shown that the probabilistic counterpart has a lower bias in estimation and is robust to non-normally distributed variables [10].…”
Section: Discussionmentioning
confidence: 99%
“…PCA was extended to Probabilistic PCA in [4], and PPLS [10] was proposed to provide a probabilistic framework for PLS. It has been shown that the probabilistic counterpart has a lower bias in estimation and is robust to non-normally distributed variables [10]. More importantly, the probabilistic model will allow statistical inference, making it possible to interpret the relevance and importance of features in the population, and facilitating follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Such analyses will provide information about the genes highly represented by the two datasets. Another extension was developed by Bouhaddani, Uh, Hayward, Jongbloed, and Houwing‐Duistermaat (2018); they embedded PLS in a probabilistic framework to facilitate statistical inference and unique identification of the parameters. One of the future directions is to compare the performance of the measurement error models and PLS methods, where the former uses additional information about the structure of the data, and the latter estimates this structure from the datasets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…An example is envelope regression (Cook and Zhang 2015), which fully models the covariance structure and is therefore not suited for high dimensional data. Alternatively, probabilistic PLS (PPLS) (el Bouhaddani et al 2018a) uses a simpler covariance structure with less parameters and is applicable to high dimensional datasets. In contrast to PPLS and envelope regression, SIFA (Li and Jung 2017) models specific components.…”
Section: Introductionmentioning
confidence: 99%